The Impact of Artificial Intelligence Language Learning Tools on Enhancing EFL learners’ Oral Reading Fluency: An Empirical Study - Al-husban, Naima; Alabri, Khalaf (Universitas Negeri Makassar, 2025)
This study aims to investigate the impact of AI language learning tools on the development of oral reading fluency among English as a Foreign Language (EFL) students and their perceptions of employing these tools during reading practice. The participants comprised 40 students who were randomly assigned to either an experimental group or a control group. The experimental group received instruction and assessment through an AI tool, specifically the Reading Progress features embedded in Microsoft Teams, whereas the control group was taught using traditional methods. Participants’ oral reading fluency was assessed to evaluate improvements both in general oral reading fluency and against established reading fluency standards. Furthermore, interviews were conducted to gather insights into students' perceptions regarding the use of the AI tool. The findings indicated that the experimental group significantly outperformed the control group in terms of reading fluency performance. Moreover, participants in the experimental group expressed positive perceptions of employing the AI tool to enhance their oral reading fluency. Based on these results, it is essential to integrate AI tools into the teaching and assessment process of English as a foreign language. Furthermore, teachers should receive professional training programs focused on designing activities for language learning in general, and specifically for oral reading fluency, as well as on teaching and evaluating students' oral reading fluency through AI tools.